2022
DOI: 10.3390/ph15101248
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Patient Preferences, Attitudes to Treatment, Adherence, and Quality of Life in New Users of Teriflunomide

Abstract: Background: A poor patient adherence often limits the real-world effectiveness of an oral disease-modifying therapy (DMT) for multiple sclerosis (MS). In the present study, we aimed to map patient preferences, attitudes toward treatment, and quality of life to identify the predictors of non-adherence to teriflunomide. Methods: This was a single-arm, non-interventional, multicenter study (Czech Act 378/2007 Coll.) consisting of three visits: the first at treatment initiation (teriflunomide 14 mg), and then afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pust et al [ 28 ] has shown that first-line patients, with less necessity beliefs for treatment, are at risk of being non-adherent patients. However, studies conducted by Thach et al [ 27 ] and Strosova et al [ 34 ] did not confirm these correlations.…”
Section: Discussionmentioning
confidence: 91%
“…Pust et al [ 28 ] has shown that first-line patients, with less necessity beliefs for treatment, are at risk of being non-adherent patients. However, studies conducted by Thach et al [ 27 ] and Strosova et al [ 34 ] did not confirm these correlations.…”
Section: Discussionmentioning
confidence: 91%